Proceedings of the 1st International Conference on Applied Economics and Social Science (ICAESS 2019) 2019
DOI: 10.2991/icaess-19.2019.58
|View full text |Cite
|
Sign up to set email alerts
|

Jakarta's Tourism Competitiveness: An Environmental Perspective

Abstract: The competitiveness of tourism destinations is important to have, so they can maintain tourism sustainability that provides economic, social and environmental benefits. Environmental problems that arise in the implementation of tourism activities make the environmental dimension as one of crucial the dimensions of competitiveness. Jakarta as a tourist destination visited by many tourists must pay attention to the competitiveness of its environment. The results of the correlation calculation between the amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Maintenance of the environmental quality could keep the environmental services and the beauty of nature and enjoying the natural resources can give relaxation conditions for tourists. That is why, the sustainability of the tourist destination becomes more important (Ismail et al, 2019). In climate change consideration, the weather has a decisive influence on the variability of the daily flow of tourists (R.-Toubes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of the environmental quality could keep the environmental services and the beauty of nature and enjoying the natural resources can give relaxation conditions for tourists. That is why, the sustainability of the tourist destination becomes more important (Ismail et al, 2019). In climate change consideration, the weather has a decisive influence on the variability of the daily flow of tourists (R.-Toubes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The result of research on the development of Tidore Island as a tourist destination found that collaboration with third parties become the key strategy (Runtunuwu, 2020). Tourism development must fulfill sustainable development, considering that tourism is an industry that must protect nature or the environment to be able to provide tourism services (Ismail et al, 2019).…”
Section: Discussionmentioning
confidence: 99%